Technological Mineralogical Analysis and Flotation Test of a Refractory Lead-zinc Ore in Hebei - Guanglin QIN; Guangsheng LI; Xingfu ZHU; Qiang JI; Congquan YU (Kuangchan zonghe liyong, 2024)
This is an article in the field of mineral processing engineering. The main valuable elements in a lead-zinc mine in Hebei are lead and zinc, with grades of 1.07% and 2.08%, respectively. Lead in the ore mainly occurs in sulfide galena, and lead-containing minerals such as galena, lead sulfate and lead jarosite. Zinc mainly occurs in sulfide sphalerite, accounting for 66.96% of the total zinc, followed by zinc oxide minerals, with high zinc oxidation rate. In the experimental study, the process of preferential flotation of lead and then zinc at the condition of grinding fineness of -200 mesh content of 65% was determined. The yield of lead concentrate is 1.74%, the grades of lead, zinc and copper in lead concentrate are 51.73%, 10.86% and 3.81%, respectively, and the recoveries are 83.93%, 8.98% and 68.20%, respectively. The yield of zinc concentrate is 2.26%, the grades of lead, zinc and copper in zinc concentrate are 1.25%, 51.64% and 0.73%, respectively, and the recoveries are 2.63%, 55.42% and 16.97%, respectively.